Reproductive function in female patients with Hodgkin's lymphoma and possibilities of its preservation - I. V. Pylova; Ye. A. Demina; R. G. Shmakov; Ye. Ye. Perilova (Онкогематология)
The impact of various Hodgkin's lymphoma treatment program on the female reproductive function is discussed. The current Russian and foreign literature on this problem is reviewed. Reproductive function was estimated in 247 females with Hodgkin's lymphoma before and after treatment. The irregular menstrual cycle in untreated group of the females with Hodgkin's lymphoma was significantly more frequent when B-symptoms were present (p = 0.0004). Radiotherapy without irradiation of inguinal and iliac areas did not induce amenorrhea irrespective of age, the number of fields and the cumulative local dose per field (as high as 50 Gy). Irradiation of inguinal and iliac areas induced amenorrhea in all females even when low doses (less than 30 Gy) were used. The ABVD treatment program did not result in steady-state ovarian tissue damage. The therapy schedules containing less than 8 g of cyclophosphamide were less toxic to ovarian tissue amenorrhea occurred only in 10.5% of the women. Treatment by the schedules with doses of cyclophosphamide more than 8 g caused amenorrhea in 26.6% of the patients. A high correlation was found between the incidence of amenorrhea and the patient' age (p = 0.0002): in women above 25 years irreversible ovarian tissue damage was revealed in 48.4% of cases.